Association of income and educational levels on initiation of oral anticoagulant therapy in patients with incident atrial fibrillation: A Finnish nationwide cohort study - Teppo Konsta; Jaakkola Jussi; Biancari Fausto; Halminen Olli; Linna Miika; Haukka Jari; Putaala Jukka; Mustonen Pirjo; Kinnunen Janne; Hartikainen Juha; Airaksinen KE Juhani; Lehto Mika (Wiley, 2022)
Aims: Socioeconomic disparities have been reported in the outcomes of patients with atrial fibrillation (AF). We assessed the hypothesis that AF patients with higher income or educational level are more frequently initiated with oral anticoagulant (OAC) therapy for stroke prevention.
Methods: The nationwide registry-based Finnish AntiCoagulation in Atrial Fibrillation cohort covers all patients with AF from all levels of care in Finland. Patients were divided into income quartiles according to their highest annual income during 2004-2018 and into three categories based on educational attainment. The outcome was the first redeemed OAC prescription.
Results: We identified 239 222 patients (mean age 72.7 ± 13.2 years, 49.8% female) with incident AF during 2007-2018. Higher income was associated with higher OAC initiation rate: compared to the lowest income quartile the adjusted SHRs (95% CI) for OAC initiation were 1.09 (1.07-1.10), 1.13 (1.11-1.14) and 1.13 (1.12-1.15) in the second, third and fourth income quartiles, respectively. Patients in the highest educational category had a slightly lower OAC initiation rate than patients in the lowest educational category (adjusted SHR 0.92 [95% CI 0.90-0.93]). Income-related disparities were larger and education-related disparities only marginal among patients at high risk of ischemic stroke. The socioeconomic disparities in OAC initiation within 1-year follow-up decreased from 2007 to 2018. The adoption of direct OACs as the initial anticoagulant was faster among patients with higher income or educational levels.
Conclusion: These findings highlight potential missed opportunities in stroke prevention, especially among AF patients with low income, whereas the education-related disparities in OAC initiation appear controversial.